Implications for the mesopelagic microbial gardening hypothesis as determined by experimental fragmentation of Antarctic krill fecal pellets - Cavan, Emma L. (Ecol Evol, 2020)
1. Detritivores need to upgrade their food to increase its nutritional value. One method is to fragment detritus promoting the colonization of nutrient‐rich microbes, which consumers then ingest along with the detritus; so‐called microbial gardening. Observations and numerical models of the detritus‐dominated ocean mesopelagic zone have suggested microbial gardening by zooplankton is a fundamental process in the ocean carbon cycle leading to increased respiration of carbon‐rich detritus. However, no experimental evidence exists to demonstrate that microbial respiration rates are higher on recently fragmented sinking detrital particles. 2. Using aquaria‐reared Antarctic krill fecal pellets, we showed fragmentation increased microbial particulate organic carbon (POC) turnover by 1.9×, but only on brown fecal pellets, formed from the consumption of other pellets. Microbial POC turnover on un‐ and fragmented green fecal pellets, formed from consuming fresh phytoplankton, was equal. Thus, POC content, fragmentation, and potentially nutritional value together drive POC turnover rates. 3. Mesopelagic microbial gardening could be a risky strategy, as the dominant detrital food source is settling particles; even though fragmentation decreases particle size and sinking rate, it is unlikely that an organism would remain with the particle long enough to nutritionally benefit from attached microbes. We propose “communal gardening” occurs whereby additional mesopelagic organisms nearby or below the site of fragmentation consume the particle and the colonized microbes. 4. To determine how fragmentation impacts the remineralization of sinking carbon‐rich detritus and to parameterize microbial gardening in mesopelagic carbon models, three key metrics from further controlled experiments and observations are needed; how particle composition (here, pellet color/krill diet) impacts the response of microbes to the fragmentation of particles; the nutritional benefit to zooplankton from ingesting microbes after fragmentation along with identification of which essential nutrients are being targeted; how both these factors vary between physical (shear) and biological particle fragmentation.